ANALISIS PENGARUH PROMOSI, LOKASI, PELAYANAN DAN SUKU BUNGA TERHADAP KEPUTUSAN PENGAMBILAN PEMBIAYAAN KREDIT USAHA RAKYAT (KUR) PADA BANK BRI CABANG KEBUME - Feby Evelyna (Sekolah Tinggi Pariwisata Mataram, 2022)
The purpose of this study is to analyze the effect of promotion, location, service and interest rates on the decision to make financing for people's business credit (KUR) BRI branch Kebumen, either partially or simultaneously. This research is a survey research with 100 respondents who are customers of Bank BRI branch Kebumen. The research method is quantitative, the data obtained are based on the answers from the respondents to the questionnaire, which are then tested for validity and reliability, while the data analysis uses multiple linear regression analysis (t test and F test), which has previously been tested for analysis prerequisites including normality, multicollinearity tests, and heteroscedasticity. After analyzing the data, the following results and conclusions were obtained. Promotion had a significant effect on the decision to make KUR financing for BRI branch Kebumen. (2) Location has a significant effect on the decision to make KUR financing for BRI branch Kebumen. (3) Service does not have a significant effect on the decision to make KUR financing for BRI branch Kebuemn. (4) Interest rates have a significant effect on the decision to make KUR financing for BRI branch Kebumen. (5) Promotion, location, service, and interest rates simultaneously have a significant effect on the decision to make KUR financing for BRI branch Kebumen